KAJIAN ETNOBOTANI TUMBUHAN OBAT DI DESA SEKABUK KECAMATAN SADANIANG KABUPATEN PONTIANAK - nardo, Leo; H. Usman, Fadillah; Yusro, Fathul (Universitas Tanjungpura, 2013)
Aim of the research was to determine of medicinal plants and their utilization of sekabuk village Sadaniang sub district Pontianak regency. Method of the research is descriptive with interview technical , and data was analyzed to obtain plants species, families, parts used, method of processing, form of the herb, dosage, method of use and type of disease that can be treated. The results showed that were 51 species and 37 families of medicinal plants used. From 51 species of medicinal plants 17 species (33.33%) is trees, 41 species (80.39%) is single plants , 22 species (43.14%) used is leaf 25 species (49.02%) used by boiling, 23 species (45.10%) used by drink and 29 species (56.86%) used to treatment of inter diseases. Keywords: Ethnobotany, medicinal plants, Sekabuk village